Benign paroxysmal torticollis of infancy: An underdiagnosed condition. (3rd February 2015) - Hadjipanayis, Adamos; Efstathiou, Elisavet; Neubauer, David
<x xml:space="preserve">Abstract</x> Benign paroxysmal torticollis is probably an under‐diagnosed condition of infancy. It is a self‐limiting disorder characterised by periods of unusual, sustained posture of the head and neck, during which the head tilts to one side. Episodes are often accompanied by marked autonomic features, irritability, ataxia, apathy and drowsiness. They last several hours to a few days and are often recurring every few weeks. They subside within the pre‐school years; however, during later childhood, there is a tendency to develop migraine. Three cases of benign paroxysmal torticollis are presented and are compared with cases in the literature. A telephone survey has been conducted to determine what is the general awareness of paediatricians of this condition in Cyprus. Eighty‐two paediatricians were randomly selected out of 235 paediatricians. All of them agreed to participate. Our cases revealed that benign paroxysmal torticollis may coexist with other problems during infancy. The telephone survey showed that only two out of eighty‐two (2.4%) of the paediatricians are aware of the condition, and none of them was confident regarding the management. Our telephone survey clearly shows that Cypriot paediatricians are not familiar with benign paroxysmal torticollis in infancy which is a benign, self‐limiting disorder. It is essential to recognise the condition and to reassure parents of its benign course and not to be misdiagnosed for other disorders, such as epileptic seizures. We have shown again that benign paroxysmal torticollis in infancy may coexist with motor delay and hearing problems.